Human NK Cells and Herpesviruses: Mechanisms of Recognition, Response and Adaptation - Della Chiesa, Mariella; De Maria, Andrea; Muccio, Letizia; Bozzano, Federica; Sivori, Simona; Moretta, Lorenzo (Frontiers in Microbiology, 2019)
NK cells contribute to early defenses against viruses through their inborn abilities that include sensing of PAMPs and inflammatory signals such as cytokines or chemokines, recognition and killing of infected cells through activating surface receptors engagement. Moreover, they support adaptive responses via Ab-dependent mechanisms, triggered by CD16, and DC editing. Their fundamental role in anti-viral responses has been unveiled in patients with NK cell deficiencies suffering from severe Herpesvirus infections. Notably, these infections, often occurring as primary infections early in life, can be efficiently cleared by NK, T and B cells in healthy hosts. Herpesviruses however, generate a complicated balance with the host immune system through their latency cycle moving between immune control and viral reactivation. This lifelong challenge has contributed to the development of numerous evasion mechanisms by Herpesviruses, many of which devoted to elude NK cell surveillance from viral reactivations rather than primary infections. This delicate equilibrium can be altered in proportions of healthy individuals promoting virus reactivation and, more often, in immunocompromised subjects. However, the constant stimulus provided by virus-host interplay has also favored NK-cell adaptation to Herpesviruses. During anti-HCMV responses, NK cells can reshape their receptor repertoire and function, through epigenetic remodeling, and acquire adaptive traits such as longevity and clonal expansion abilities. The major mechanisms of recognition and effector responses employed by NK cells against Herpesviruses, related to their genomic organization will be addressed, including those allowing NK cells to generate memory-like responses. In addition, the mechanisms underlying virus reactivation or control will be discussed.